Association between anterior open bite and pacifier sucking habit in schoolchildren in a city of southern Brazil - Claudiane Tibolla; Lilian Rigo; Lincoln Issamu Nojima; Anamaria Estacia; Eduardo Gianoni Frizzo; Leodinei Lodi (Dental Press Editora, 2012)
OBJECTIVE: The objective of this study was to verify from a school-based epidemiological survey, the prevalence of anterior open bite, analyzing the influence of pacifier habit in the school. METHODS: The first step was a questionnaire for the parents, and later clinical examinations in 237 school children, 3-14 years old, in the city of Santo Expedito do Sul/RS, Brazil. RESULTS: The population gender distribution was 50.3% boys and 49.4% girls with a mean age of 8.63 years, and 16% had primary dentition, 50.2% mixed dentition and 33.8 % permanent dentition. There was a 22.8% prevalence of anterior open bite, obtaining a significant association between anterior open bite and the pacifier sucking habit on the three dentitions. CONCLUSION: The duration and frequency of the habit were strongly associated with anterior open bite malocclusion in the deciduous and mixed dentitions. OBJETIVO: o objetivo deste estudo foi verificar, a partir de um levantamento epidemiológico de base escolar, a prevalência de mordida aberta anterior, analisando a influência do hábito da chupeta no seu estabelecimento. MÉTODOS: na primeira etapa, foi aplicado um questionário aos responsáveis e, posteriormente, foram feitos exames clínicos em 237 escolares de 3 a 14 anos do município Santo Expedito do Sul/RS. RESULTADOS: o tamanho da população, segundo o sexo, foi de 50,3% meninos e 49,4% meninas, com média de idade de 8,6 anos, sendo que 16% possuíam dentição decídua; 50,2%, dentição mista; e 33,8%, dentição permanente. Verificou-se uma prevalência de 22,8% de mordida aberta anterior, obtendo-se associação significativa entre a mordida aberta anterior e o hábito de sucção de chupeta, nas três dentições. CONCLUSÃO: a duração e a frequência do hábito estiveram fortemente associadas à má oclusão de mordida aberta anterior nas dentições decídua e mista.